Calcium Regulates Molecular Interactions of Otoferlin with Soluble NSF Attachment Protein Receptor (SNARE) Proteins Required for Hair Cell Exocytosis - Ramakrishnan, Neeliyath A. (American Society for Biochemistry and Molecular Biology, 2014)
Mutations in otoferlin, a C2 domain-containing ferlin family protein, cause non-syndromic hearing loss in humans (DFNB9 deafness). Furthermore, transmitter secretion of cochlear inner hair cells is compromised in mice lacking otoferlin. In the present study, we show that the C2F domain of otoferlin directly binds calcium (K(D) = 267 μm) with diminished binding in a pachanga (D1767G) C2F mouse mutation. Calcium was found to differentially regulate binding of otoferlin C2 domains to target SNARE (t-SNARE) proteins and phospholipids. C2D–F domains interact with the syntaxin-1 t-SNARE motif with maximum binding within the range of 20–50 μm Ca(2+). At 20 μm Ca(2+), the dissociation rate was substantially lower, indicating increased binding (K(D) = ∼10(−9)) compared with 0 μm Ca(2+) (K(D) = ∼10(−8)), suggesting a calcium-mediated stabilization of the C2 domain·t-SNARE complex. C2A and C2B interactions with t-SNAREs were insensitive to calcium. The C2F domain directly binds the t-SNARE SNAP-25 maximally at 100 μm and with reduction at 0 μm Ca(2+), a pattern repeated for C2F domain interactions with phosphatidylinositol 4,5-bisphosphate. In contrast, C2F did not bind the vesicle SNARE protein synaptobrevin-1 (VAMP-1). Moreover, an antibody targeting otoferlin immunoprecipitated syntaxin-1 and SNAP-25 but not synaptobrevin-1. As opposed to an increase in binding with increased calcium, interactions between otoferlin C2F domain and intramolecular C2 domains occurred in the absence of calcium, consistent with intra-C2 domain interactions forming a “closed” tertiary structure at low calcium that “opens” as calcium increases. These results suggest a direct role for otoferlin in exocytosis and modulation of calcium-dependent membrane fusion.